Annoyance penalty of impulsive noise – The effect of impulse onset. (15th January 2020) - Rajala, Ville; Hongisto, Valtteri
Abstract: Impulsive sound can be perceived more annoying than a steady-state sound having the same A-weighted equivalent sound pressure level, L Aeq . The difference in perceived noise annoyance can be compensated by adding a penalty or an adjustment k to L Aeq (rating level). Many legislations apply a constant penalty value, such as 5 dB or more, but the validity of this procedure has been questioned. Nordtest method NT ACOU 112 identifies an impulse from the time profile of sound pressure level by using two measures describing the onset of an impulse: level difference ( D L ) and onset rate ( R on ). The purpose of this study was to determine how the annoyance penalty depends on D L (5–40 dB) and R on (5–800 dB/s) and to compare obtained results to the penalty prediction model of Nordtest method. A psychoacoustic laboratory experiment of 32 participants was conducted. Synthetic and periodic impulsive sounds were studied with two alternative spectra. The sounds were presented at 55 dB L Aeq . Steady-state sounds at levels 49–70 dB were used to derive the penalty of impulsive sounds. The observed penalty values ranged between 0 and + 8 dB. The penalty values depended somewhat on spectrum. The penalty deviated from zero when D L  > 10 dB or R on > 15 dB/s and increased with increasing D L and R on . The penalty predicted by Nordtest method usually overestimated the observed penalty when R on ≥ 200 dB/s. The results are against constant penalty values and they can be used to develop future penalty schemes. Highlights: Impulsive noise is more annoying than steady-state noise and deserves a penalty. Our results were against constant penalty values used in most noise regulations. Penalty values ranged from 0 to 8 dB depending on the prominence of the impulse. Prominence depends on impulse envelope: onset rate and level difference. Results can be used to assess the annoyance of impulsive noise in buildings.